FACTORES QUE INFLUYEN EN EL NIVEL DE SATISFACCIÓN DE LOS TURISTAS EXTRANJEROS QUE VISITAN CUSCO - Domínguez Díaz, Carmen (2008)
In the present work, we determine the most important factors in the nivel of satisfaction of foreign tourists, and the intention of recommendation of the tourists who visit the city of the Cusco using multivariate methods such as the Multiple Logistic Regression Model (7). The data used correspond to the survey conducted by the company Corporación de Compañías de Research CCR, on behalf of PROMPERÚ, in 2003.